Mechanistic insights into effects of the cardiac myosin activator omecamtiv mecarbil from mechanokinetic modelling - Månsson, Alf (Frontiers in Physiology, 2025)
IntroductionSmall molecular compounds that affect the force, and motion-generating actin-myosin interaction in the heart have emerged as alternatives to treat or alleviate symptoms in severe debilitating conditions, such as cardiomyopathies and heart failure. Omecamtiv mecarbil (OM) is such a compound developed to enhance cardiac contraction. In addition to potential therapeutic use, its effects may help to elucidate myosin energy transduction mechanisms in health and disease and add insights into how the molecular properties govern contraction of large myosin ensembles in cardiac cells. Despite intense studies, the effects of OM are still incompletely understood.MethodsHere we take an in silico approach to elucidate the issue. First, we modify a model, previously used in studies of skeletal muscle, with molecular parameter values for human ventricular β-myosin to make it useful for studies of both myosin mutations and drugs. Repeated tests lead to at a set of parameter values that allow faithful reproduction of range of functional variables of cardiac myocytes. We then apply the model to studies of OM.Results and discussionThe results suggest that major effects of OM such as large reduction of the maximum velocity with more limited effects on maximum isometric force and slowed actin-activated ATPase can be accounted for by two key molecular effects. These encompass a reduced difference in binding free energy between the pre- and post-power-stroke states and greatly increased activation energy for the lever arm swing during the power-stroke. Better quantitative agreement, e.g., isometric force minimally changed from the control value by OM is achieved by additional changes in model parameter values previously suggested by studies of isolated proteins.